La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)
fs-ref-orig: Bouchard, L., Batal, M., Imbeault, P., Gagnon-Arpin, I., Makvandi, E., & Sedigh, G. (2012). The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS). Réseau de recherche appliquée sur la santé des francophones de l'Ontario. fs-code-orig: Bouchard-2012d

L'offre active des services de santé en français en Ontario : une mesure d'équité - Bouchard, Louise; Beaulieu, Marielle; Desmeules, Martin (Reflets, 2012)
Cet article fait état d’une recherche sur l’offre active de services en français en Ontario. L’étude avait pour objectifs de recenser les définitions de l’offre active de services en français; d’identifier les pratiques d’offre active (facilitateurs ou obstacles); d’identifier les indicateurs de mesure de l’offre active et de proposer des recommandations permettant d’améliorer l’offre active de services en français. À cette fin, une revue documentaire, une enquête auprès de professionnels oeuvrant dans le domaine de la planification des services de santé en français ainsi qu’un atelier de cartographie conceptuelle ont été entrepris. Mots-clés : minorité linguistique, services de santé, offre active, Loi 8

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)
fs-ref-orig: Bouchard, L., Gagnon-Arpin, I. et Makvandi, E. (2012). Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est. Réseau de recherche appliquée sur la santé des francophones de l’Ontario. fs-code-orig: Bouchard-2012e

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

Linguistic variables: A necessity for health services planning tailored to the needs of Francophones. Current Status - French Language Heatlh Services Network of Eastern Ontario (Current Status, 2012)
fs-ref-orig: French Language Heatlh Services Network of Eastern Ontario. (2012). Linguistic variables: A necessity for health services planning tailored to the needs of Francophones. Current Status. fs-code-orig: French Language Heatlh Services Network of Eastern Ontario-2012

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.